Photocathode optimization and microbial community in the solar-illuminated bio-photoelectrochemical system for nitrofurazone degradation. (April 2020) - Hou, Yanping; Yuan, Guiyun; Qin, Shanming; Tu, Lingli; Yan, Yimin; Yu, Zebin; Lin, Hongfei; Chen, Yongli; Zhu, Hongxiang; Song, Hainong; Wang, Shuangfei
Graphical abstract: Highlights: The g-C3 N4 /CdS photocathode in the bio-photoelectrochemical system was optimized. The performance of bio-photoelectrochemical system was further enhanced with the optimized photocathode. The microbial community shift from inoculation to the bio-photoelectrochemical system was revealed. Proteobacteria, was the most dominant phylum, accounting for 74.67% in bio-photoelectrochemical system anode. Abstract: To further enhance the bio-photoelectrochemical system (BPES) performance for nitrofurazone (NFZ) degradation and current output, the g-C3 N4 /CdS photocathode was optimized, and microbial community shift from inoculation to the BPES was analyzed. Results showed that photocathode with g-C3 N4 /CdS (mass ratio of 1:9) loading of 7.5 mg/cm 2 exhibited the best performance, with NFZ removal of 83.14% (within 4 h) and current of 9 mA in the BPES. Proteobacteria accounted for the largest proportion: 66.53% (inoculation), 71.89% (microbial electrolysis cell (MEC) anode), 74.67% (BPES anode) and 57.31% (BPES cathode), respectively. In addition, Geobacter was the most dominant genus in MEC and BPES anode and cathode, which occupied 31.64%, 67.73% and 41.34%, respectively. The microbial compositions of BPES anode and cathode were similar, but different from that of MEC anode. Notably, Rhodopseudomonas, a photosynthetic species, was detected in the BPES. Cognition of microbial community in the BPES is important for advancing its development.